Strategi Edukasi Pengelolaan Sampah Oleh Kader PKK Untuk Meningkatkan Kebersihan Lingkungan di Desa Pulosari - Siti Napsiyah Arifuzzaman; Almira Al Rayyan; Muhammad Adam Farros; Mohammad Azidan; Nurul Aulia Asifa; Salsabila Nur Rizky (LPPI UMN AL WASHLIYAH, 2025)
Waste management is a significant challenge in Indonesia, including in Pulosari Village, Bandung Regency. This study aims to analyze the waste management education strategy implemented by PKK Cadres to improve environmental cleanliness in Pulosari Village. Using a qualitative approach with descriptive methods, this research involved semi-structured interviews, observations, and literature studies. The results show that PKK Cadres play a crucial role in raising community awareness through various educational programs, including socialization at integrated health posts, religious gatherings, and community meetings. The strategies implemented include waste sorting training, cleanliness campaigns, and the